Integration of Religion, Science and Islamic Epistemology - Nur Itsnaini Yasyifa Nasyrah; Maspuroh; Nia Nuraeni; Nisa Ramadhani; Wildan Muhamad Taqiy (Penerbit Hellow Pustaka, 2025)
The integration of religion and science is an important theme in education and research, which aims to create a holistic understanding of the realities of life. This research aims to describe and analyze the integration paradigm between religion and science, as well as its implications in education. The method used is qualitative research with a literature study approach. This research aims to describe and analyze the integration between religion and science from the perspective of Islamic scientific epistemology. In this context, the author uses a qualitative approach with a literature study method to examine the views of Islamic scholars who focus on the integration of science and religion. This journal discusses the integration of religion, science and Islamic scientific epistemology in a modern context. By putting forward the view that science and religion do not conflict with each other, this article explores how Islamic principles can provide a moral and ethical foundation for the development of science. Through an interdisciplinary approach, this article analyzes several important aspects, including the relationship between revelation and reason, as well as how scientific methods can be enriched with a spiritual perspective. In this context, this research also highlights the role of Islamic epistemology in shaping the perspective of Muslim scientists towards natural phenomena. It is hoped that the results of this study can strengthen dialogue between science and religion, as well as encourage the development of science oriented towards Islamic values.